2006
DOI: 10.1007/s00425-006-0441-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of sll1383 from Synechocystis sp PCC 6803 as L-myo-inositol 1-phosphate phosphatase (EC 3.1.3.25): molecular cloning, expression and characterization

Abstract: The genome sequence of the cyanobacterium Synechocystis sp. PCC6803 revealed four Open reading frame (ORF) encoding putative inositol monophosphatase or inositol monophosphatase-like proteins. One of the ORFs, sll1383, is approximately 870 base pair long and has been assigned as a probable myo-inositol 1 (or 4) monophosphatase (IMPase; EC 3.1.3.25). IMPase is the second enzyme in the inositol biosynthesis pathway and catalyses the conversion of L-myo-inositol 1-phosphate to free myo-inositol. The present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…The apparent V max for VTC4 with D-Ins 3-P was 4.0 units and that for L-Gal 1-P was 5.4 units. In general, these kinetic parameters are comparable to those found for the Lilium IMP (K m of 78 mM for D-Ins 3-P; Loewus and Loewus, 1982) and kiwifruit VTC4 (K m of 150 mM for L-Gal 1-P and 330 mM for D-Ins 3-P; Laing et al, 2004; Table II), yet they differ from the previously reported values for the Synechocystis (Patra et al, 2007) and barley (Hordeum vulgare) enzymes (Fu et al, 2008), which have lower K m values (Table II). Furthermore, the ratio of V max to K m provides one measure of discriminating substrate preference, and we found that there is a 1.7-fold difference in the ratios, indicating a small difference between L-Gal 1-P and D-Ins 3-P (Table II).…”
Section: Expression Of Recombinant Atvtc4 Proteinsupporting
confidence: 81%
“…The apparent V max for VTC4 with D-Ins 3-P was 4.0 units and that for L-Gal 1-P was 5.4 units. In general, these kinetic parameters are comparable to those found for the Lilium IMP (K m of 78 mM for D-Ins 3-P; Loewus and Loewus, 1982) and kiwifruit VTC4 (K m of 150 mM for L-Gal 1-P and 330 mM for D-Ins 3-P; Laing et al, 2004; Table II), yet they differ from the previously reported values for the Synechocystis (Patra et al, 2007) and barley (Hordeum vulgare) enzymes (Fu et al, 2008), which have lower K m values (Table II). Furthermore, the ratio of V max to K m provides one measure of discriminating substrate preference, and we found that there is a 1.7-fold difference in the ratios, indicating a small difference between L-Gal 1-P and D-Ins 3-P (Table II).…”
Section: Expression Of Recombinant Atvtc4 Proteinsupporting
confidence: 81%
“…Recently Patra et al (2007) isolated sequences encoding an IMPase from the cyanobacterium Synechocystis sp. PCC6803, and studied the catalytic properties of the recombinant protein.…”
Section: Discussionmentioning
confidence: 99%
“…Chhetri et al (2005Chhetri et al ( , 2006 have already established the occurrence of the prime enzyme of myo-inositol biosynthesis, MIPS, in pteridophytes. Therefore, the presence of MIPP adds (Eisenberg Jr. 1967, Attwood et al, 1988Gee et al, 1988;Honchar et al, 1989;Leech et al, 1993;Pollack et al, 1994;Caselli et al, 1996, Fujimoto et al, 1996, Nigou and Besra, 2002Wang et al, 2006;Patra et al, 2007). However, its kinetic parameter, thermo-tolerance and calciumdependent inhibition at lower concentrations, differ substantially in pteridophytic species.…”
Section: Discussionmentioning
confidence: 99%
“…In pteridophytes, Benaroya et al (2004) and Chettri et al (2005Chettri et al ( , 2006 have recently documented the occurrence and characterization of L-myo-inositol-1-phosphate synthase. So far, work with regard to the participation of the subsequent enzyme in this metabolic sequence, myo-inositol-1-phosphate phosphatase (MIPP), has been carried out principally in animal systems (Eisenberg Jr, 1967;Attwood et al, 1988;Gee et al, 1988;Honchar et al, 1989;Leech et al, 1993;Pollack et al, 1994;Kwok and Lo, 1994;Fujimoto et al, 1996;Caselli et al, 1996), in archaea (Wang et al, 2006), in bacteria (Nigou and Besra, 2002), and in cyanobacteria (Patra et al, 2007). However, only a few reports are available of this enzyme from plant systems (Loewus and Loewus, 1983;Gumber et al, 1984).…”
Section: Introductionmentioning
confidence: 99%